Peripherally inserted central catheter insertion and management in Hodgkin and non-Hodgkin lymphomas: a 13-year monocentric experience - Derudas, Daniele; Massidda, Stefania; Simula, Maria Pina; Dessì, Daniela; Usai, Sara Veronica; Longhitano, Giuseppe; Ibba, Daniela; Aracu, Loredana; Atzori, Monica; La Nasa, Giorgio (Frontiers in Hematology, 2023)
Background Non-Hodgkin’s lymphoma (NHL) and Hodgkin’s lymphoma (HL) are two of the most common hematologic diseases that require an infusion of immunochemotherapies in conjunction with radiotherapy, often in an outpatient setting. For relapsed/refractory disease, autologous peripheral hematopoietic stem cell transplantation and sometimes allogeneic transplantation (HSCT) are considered standard treatment options. Recently, chimeric antigen receptor (CAR) T cells and bispecific antibodies have emerged as an important and effective option for the treatment of relapsed/refractory patients. These medical approaches deserve effective, safe, and durable vascular access, especially for the ambulatory population undergoing discontinuous treatment associated with high rates of complications and life-threatening toxicities. Peripherally inserted central catheters (PICCs) are vascular devices with an intermediate-to-long-term lifespan that are inserted ultrasonically into a peripheral brachial vein. Their ease of insertion by trained nurses and low rate of catheter-related infectious and thrombotic complications make them ideal devices for treating oncology and hematology patients. Purpose In this study, we aim to demonstrate that PICCs are an essential tool for the treatment of HL and NHL patients in terms of efficiency and safety Methods and results From March 2007 to June 2020, 316 PICC implantations were performed by our PICC team in 276 HL patients and 363 PICC in 322 NHL patients. The total lifespan of the PICCs was 50,660 days in HL and 43,919 days in NHL patients. Most PICCs were removed at the end of therapy, and the rate of mechanical complications was low. Only one and four episodes of confirmed PICC-related catheter-related bloodstream infections (CRBSIs) (0.3%; 0.02/1,000 days/PICC and 1.2%; 0.07/1,000 days/PICC) were recorded in HL and NHL patients, respectively. There were only 11 (3.6%; 0.25/1,000 days/PICC) and nine (2.6%; 0.17/1,000 days/PICC) episodes of symptomatic PICC-related thrombotic complications in HL and NHL patients, respectively, without removal. Conclusion Our data indicate that the PICC can be considered the device of choice for treating HL and NHL patients because it is easy to insert, safe to use, long-lasting, and has a low complication rate, especially in the outpatient setting.